2017
DOI: 10.22314/2073-7599-2017-2-31-36
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ultraviolet Radiation on Germination and Growth Processes of Wheat Seeds

Abstract: При исследовании влияния ультрафиолетового (УФ) излучения на посевные качества семян и биометрические показатели морфологических органов растений различных сельхозкультур ученые не пришли к единому мнению об оптимальных параметрах его воздействия. Мы изучили влияние ультрафиолета от источника VL-6.LC с длиной волны 365 нм в течение 5 и 30 мин на семена яровой и озимой пшеницы различных сортов. Установили, что для семян каждого сорта существует свое оптимальное количество поглощенной энергии, приводящее к макси… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…As a result of seed treated with optimal doses the seed vigor and germination are the highest. Our results confirm the data from the study by Tertyshnaya et al (2018) on examining the impact of UV-B radiation (365 nm) on seed germination of spring and winter wheat. The authors have shown that wheat germination 'Moskovskaya 39' (67 %), 'Yubileynaya 100' (92 %), 'Dar'ya' (98 %) and ' Afina' (99 %) cultivars increased by 1-3 % as a result of seed treatment.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As a result of seed treated with optimal doses the seed vigor and germination are the highest. Our results confirm the data from the study by Tertyshnaya et al (2018) on examining the impact of UV-B radiation (365 nm) on seed germination of spring and winter wheat. The authors have shown that wheat germination 'Moskovskaya 39' (67 %), 'Yubileynaya 100' (92 %), 'Dar'ya' (98 %) and ' Afina' (99 %) cultivars increased by 1-3 % as a result of seed treatment.…”
Section: Resultssupporting
confidence: 90%
“…The values of seed vigour and germination after treatment compared with the control were founded higher of about 37 % and 30 %, respectively. The effect of UV-C irradiation (200-280 nm) on biometric parameters of the wheat cultivars studied by us turned out to be more significant than that described in study Tertyshnaya et al (2018). As it was established in our experiments, the length of seedlings roots of all the investigated seed cultivars increased by 2-3.6 times, and height of shoots -by 2.0-3.4 times, while the authors of study Tertyshnaya et al (2018) observed increasing the root length of wheat seedlings treated with UV-B rays (365 nm) by only 26-60 %.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…According to Tertyshnaya et al (2017), the research results could be more consistent regarding the effects of different UV radiation exposure and doses on plant seeds. This physical exposure has no demonstrable effect on seed germination of the examined wheat varieties, but the biometric characteristics of developing plants will be signi cantly altered.…”
Section: Discussionmentioning
confidence: 86%
“…A positive effect of pre-sowing treatment with ultraviolet irradiation on the sowing qualities of seeds was noted [4][5][6][7][8][9]. Koshkina O.A.…”
Section: Introductionmentioning
confidence: 99%